2018
DOI: 10.3389/fnins.2018.00737
|View full text |Cite
|
Sign up to set email alerts
|

Awake fMRI Reveals Brain Regions for Novel Word Detection in Dogs

Abstract: How do dogs understand human words? At a basic level, understanding would require the discrimination of words from non-words. To determine the mechanisms of such a discrimination, we trained 12 dogs to retrieve two objects based on object names, then probed the neural basis for these auditory discriminations using awake-fMRI. We compared the neural response to these trained words relative to “oddball” pseudowords the dogs had not heard before. Consistent with novelty detection, we found greater activation for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…Brain areas responding to human speech were identified here using various speech sounds and voices (all acoustic stimuli versus silence contrast of Model 1). These areas were highly similar to those found in previous dog fMRI studies using one speaker as stimulus 32,38,46 . Using an fMRI adaptation paradigm, we demonstrated that among speech-responsive cortical regions secondary (cESG), but not primary (mESG), auditory areas exhibited short-term repetition effects.…”
Section: Discussionsupporting
confidence: 87%
“…Brain areas responding to human speech were identified here using various speech sounds and voices (all acoustic stimuli versus silence contrast of Model 1). These areas were highly similar to those found in previous dog fMRI studies using one speaker as stimulus 32,38,46 . Using an fMRI adaptation paradigm, we demonstrated that among speech-responsive cortical regions secondary (cESG), but not primary (mESG), auditory areas exhibited short-term repetition effects.…”
Section: Discussionsupporting
confidence: 87%
“…The auditory network identified in our study corresponds with the primary auditory cortex in dogs and auditory RSN identified in awake dogs [17]. Activation of this area by sound has been shown in previous studies in awake unrestrained dogs [14,56]. While Andics and colleagues showed common functions in dog and human voice processing [14], Prichard et al reported that most dogs were able to discriminated pseudo-words from trained words [56].…”
Section: Discussionsupporting
confidence: 78%
“…Activation of this area by sound has been shown in previous studies in awake unrestrained dogs [14,56]. While Andics and colleagues showed common functions in dog and human voice processing [14], Prichard et al reported that most dogs were able to discriminated pseudo-words from trained words [56]. Interestingly, in anaesthetised dogs, Bach and colleagues found only subcortical but no cortical response to auditory stimuli [36].…”
Section: Discussionmentioning
confidence: 91%
“…Beyond our previous study on dogs’ lexical processing 9 , there have been two recent dog fMRI studies that used words as stimuli, but neither of these two was designed to reveal lexical effects. One study found an increased activity for novel pseudowords compared to trained words in the broadly defined parietotemporal cortex, but that effect was related to novelty processing rather than to lexical processing 47 . The other study showed that stimulus-reward neural associations are formed less effectively for verbal than for visual or olfactory cues 48 .…”
Section: Introductionmentioning
confidence: 99%